DAMPAK KEMAMPUAN KEUANGAN DAN PENGALAMAN KEUANGAN TERHADAP PENGAMBILAN KEPUTUSAN KEUANGAN MELALUI KEBERLANJUTAN BISNIS PADA PELAKU UMKM - Naim, Muh. Rezky; Novitasari, Eni; Karmilah , Karmilah (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
The purpose of this study is to examine how financial capability and financial experience influence financial decision-making with business sustainability as a mediating variable among MSME actors in West Sulawesi, with a particular emphasis on the creative sector. Although MSMEs play an important role in the local economy, they still face major problems, mainly due to a lack of financial knowledge and experience in managing businesses. Financial capability refers to understanding financial basics, controlling debt, and using financial instruments. However, financial experience is defined as the accumulation of practical skills gained from business management activities, which can impact the quality of financial decision-making. This study uses a quantitative approach by conducting a survey of a number of small and medium-sized enterprises (SMEs) in West Sulawesi that were selected purposively. The research tool is a questionnaire with a five-point Likert scale. In addition, to evaluate the relationship between variables, the data is analyzed using a structural equation model (SEM) based on SmartPLS. Research shows that financial experience and knowledge have a positive and significant impact on financial decision-making. Business sustainability is also shown to be a mediating factor. This is because financial experience and capabilities influence financial decisions. The results show that training and mentoring and sustainable managerial practices are very important for improving financial knowledge and enhancing financial experience. This research not only helps develop financial management theory, but also provides practical advice for local governments, financial institutions, and small and medium-sized enterprises (SMEs) to improve their business sustainability.